Audiological outcomes of cochlear implantation in Waardenburg Syndrome - Magalhães,Ana Tereza de Matos (2013)
INTRODUCTION: The most relevant clinical symptom in Waardenburg syndrome is profound bilateral sensorioneural hearing loss. AIM: To characterize and describe hearing outcomes after cochlear implantation in patients with Waardenburg syndrome to improve preoperative expectations. METHOD: This was an observational and retrospective study of a series of cases. Children who were diagnosed with Waardenburg syndrome and who received a multichannel cochlear implant between March 1999 and July 2012 were included in the study. Intraoperative neural response telemetry, hearing evaluation, speech perception, and speech production data before and after surgery were assessed. RESULTS: During this period, 806 patients received a cochlear implant and 10 of these (1.2%) were diagnosed with Waardenburg syndrome. Eight of the children received a Nucleus 24® implant and 1 child and 1 adult received a DigiSonic SP implant. The mean age at implantation was 44 months among the children. The average duration of use of a cochlear implant at the time of the study was 43 months. Intraoperative neural responses were present in all cases. Patients who could use the speech processor effectively had a pure tone average of 31 dB in free-field conditions. In addition, the MUSS and MAIS questionnaires revealed improvements in speech perception and production. Four patients did not have a good outcome, which might have been associated with ineffective use of the speech processor. CONCLUSION: Despite the heterogeneity of the group, patients with Waardenburg syndrome who received cochlear implants were found to have hearing thresholds that allowed access to speech sounds. However, patients who received early intervention and rehabilitation showed better evolution of auditory perception.